2006
DOI: 10.1177/1420326x06063221
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Air Pollution and Meteorological Parameters on Chronic Obstructive Pulmonary Disease at an Istanbul Hospital

Abstract: In this study, the relation between emergency admissions for chronic obstructive pulmonary disease (COPD) at an Istanbul University Hospital between the years 1997 and 2001 and the meteorological and air pollution parameters has been analysed. Admissions were calculated for each month, and the relations between the number of admissions for each month and the corresponding month's meteorological parameters (pressure, temperature, moisture) and the average pollution values (CO, SO2, NO, NO2, PM10) were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Higher barometric pressure, more hours of sunshine, and lower humidity in winter were associated with an increase in chronic obstructive pulmonary disease (COPD) exacerbations in Taiwan (Tseng et al, 2013), implying that warm and dry high pressure systems were associated with COPD anomalies. In contrast, Hapçioğlu et al (2006) found no relationship between humidity and COPD exacerbations in Istanbul. A study in Trinidad (Ivey et al, 2013) supported the contention that in warm, wet climates, incidence of asthma increased with higher relative humidity in the wet season (MayDecember).…”
Section: Humidity and Pulmonary Diseasementioning
confidence: 68%
“…Higher barometric pressure, more hours of sunshine, and lower humidity in winter were associated with an increase in chronic obstructive pulmonary disease (COPD) exacerbations in Taiwan (Tseng et al, 2013), implying that warm and dry high pressure systems were associated with COPD anomalies. In contrast, Hapçioğlu et al (2006) found no relationship between humidity and COPD exacerbations in Istanbul. A study in Trinidad (Ivey et al, 2013) supported the contention that in warm, wet climates, incidence of asthma increased with higher relative humidity in the wet season (MayDecember).…”
Section: Humidity and Pulmonary Diseasementioning
confidence: 68%
“…There is increasing concern among the experts in the field over the adverse health effects of air pollution, especially in urban areas where air pollution is usually greatest. Suspended PM in particular has received much interest because of epidemiological and experimental evidence that associate PM concentrations with excesses in daily mortality and morbidity [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…27 Meteorological conditions, however, appear to have the greatest impact on daily variations in ambient air quality. 2831 Meteorology is a confounding factor, both in epidemiological research of health effects due to exposure to ambient PM 10 and in the evaluation of effects of emission reduction measures on PM 10 concentrations in the atmospheric environment. 32 In order to be able to assess the effects of local and temporarily reduction measures during episodes, such as limitation of traffic, there is a need for information about the contribution of sources and meteorology to the day-to-day variation in concentration.…”
Section: Literature Reviewmentioning
confidence: 99%